Caring for Our Caregivers: a feasibility study of caregiver preparedness training within inpatient brain injury rehabilitation. (2nd October 2020) - Stepansky, Kasey; Sethi, Amit; Toto, Pamela; Bleakley, Scott
Abstract : Background/aims: Evidence-based inpatient caregiver training may ensure that caregiver needs are met and hospital readmission costs reduced. The aim of this study was to evaluate the feasibility of implementing a caregiver education model, Caring for Our Caregivers, within an inpatient brain injury programme. Methods: A total of 32 adults were admitted to inpatient neurorehabilitation during the 7-week feasibility trial. The three-step Caring for Our Caregivers programme included evidence-based recommendations following a caregiver needs assessment, goal setting and hands-on training. Satisfaction levels and caregiver preparedness were assessed via a survey. Results: The caregiver needs assessment and goal collaboration was completed within 5 days 66% of the time. Results indicated an even distribution of hands-on (47%) and discussion-based (53%) education. Caregivers and staff identified high levels of satisfaction with the programme. Conclusions: Early engagement, collaborative goals and hands-on training of the family caregiver of a client with acquired brain injury during inpatient rehabilitation demonstrated initial feasibility with positive implications for caregiver satisfaction and community discharge.